Poor Students’ Strategies in Achieving Achievement In Favorite Schools: A Qualitative Study in Cilacap and Banyumas - Martono, Nanang; Puspitasari, Elis; Mintarti, Mintarti; Dadan, Sulyana; Sabrina, Laila (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Poor students are often considered students with difficulty achieving in school due to limited resources. Some try to study in their favorite schools, dominated by upper-class students. This study aims to describe the efforts made by poor students to achieve in their favorite schools. The qualitative research method involves interviewing poor students who excel with teachers at their favorite schools. The study results show that they are motivated to achieve and utilize the available learning facilities. They borrow books from the library and download books from the internet to learn. They also utilize free tutoring facilities that can be accessed online. Saving is their way of fulfilling learning facilities. They have a habit of practicing learning discipline at home by utilizing their free time as much as possible. The results of this study can change the negative stigma regarding poor students who are identified with laziness, helplessness, indiscipline, and failure. This study can provide insight into the efforts of poor students to develop resilience and achieve high academic achievement despite facing economic challenges.